Tellurium Effect on ASTM A 220 Graphite Malleable Cast Iron - Mohammad Nur Hidajatullah; Achmad Sambas; Khansa Sarah Puspita (Logic : Jurnal Rancang Bangun dan Teknologi, 2019)
The result of investigation of tellurium malleable cast iron are presented in the paper. Various small quantity of tellurium are added in the ladle before pouring molten metal. The main aim of investigation was determination of the influence composition of tellurium on graphite microstructure and mechanical properties. In addition, the final mechanical property of composition determined by hardness measurements. The favourable influence of the addition of tellurium into malleable cast iron molten metal on the tested properties after annealing as well as an percentation of graphite structure from 2% up to 6.5% and increase hardness from 38 HRc up to 43 HRc